1992
DOI: 10.1164/ajrccm/145.4_pt_1.954
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Vascular Permeability after Lung Transplantation: A Positron Emission Tomographic Study

Abstract: We evaluated pulmonary vascular permeability in 15 patients after lung transplantation (21 allografts) by measuring the pulmonary transcapillary escape rate (PTCER) for Ga-68-labeled transferrin, using positron emission tomography. Seven recipients (four unilateral, three bilateral lung transplants) were studied within 3 days of transplantation, and each developed hypoxemia and allograft infiltrates consistent with the "reimplantation response." PTCER was higher in subjects studied within 1 day than in those s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
37
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 5 publications
0
37
1
Order By: Relevance
“…Controversial results have been observed in clinical transplantation. A negative influence of graft ischemic time on early graft function was found by several groups including ours (6,19,20), but others have not reported similar results (4,5,21,22). The discrepancy between previous results and our data may be explained by the high statistical power of our study.…”
Section: Discussioncontrasting
confidence: 84%
“…Controversial results have been observed in clinical transplantation. A negative influence of graft ischemic time on early graft function was found by several groups including ours (6,19,20), but others have not reported similar results (4,5,21,22). The discrepancy between previous results and our data may be explained by the high statistical power of our study.…”
Section: Discussioncontrasting
confidence: 84%
“…This response has been widely studied in animal models [2][3][4][5], but few data are available in clinical lung transplantation [8][9][10]14].…”
Section: Discussionmentioning
confidence: 99%
“…This correlation was also found in animal models [3], in which prolongation of graft ischaemia increases the incidence of obvious oedema formation. KAPLAN et al [10] evaluated the pulmonary vascular permeability in 15 patients after lung transplantation by measuring a quantitative index of vascular permeability, and they found that the longer preservation time was associated with higher index values. Curiously, BAVOUX et al [9] did not find any correlation between PRR and the graft ischaemic time in 35 heart-lung recipients [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a pathophysiological mechanism accounts for the high sensitivity of 201 Tl scintigraphy (92%) observed in the present study. This is further supported by positron-emission tomographic (PET) measurements of pulmonary-transcapillary escape rate, which were reported to be elevated in patients with biopsyproven lung rejection, and decreased after immunosuppressive treatment, suggesting that pulmonary vascular permeability is, indeed, altered by the rejection/lung injury state [21].…”
Section: Discussionmentioning
confidence: 77%